Marketing to Chinese millennials: An examination of the effectiveness of UGC marketing on RED - Liu, Zhenshan; Li, Shi (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the effectiveness of user-generated content (UGC) marketing on the social commerce platform RED, focusing on Chinese millennials. It explores how content creators and consumers engage with UGC, highlighting the commercialization of content and its influence on purchasing decisions. The study uses a mixed-methods approach, combining semi-structured interviews with content creators and consumers, alongside a quantitative analysis of survey data. The entropy weight method (EWM) is employed to assess the impact of UGC on consumer trust and behavior. Content creators initially engage in UGC for informational and emotional support, but over time, many shift toward commercialization. Consumers trust UGC from influencers and ordinary users more than from celebrities, as interactions enhance credibility. High-quality UGC, offering detailed and authentic product reviews, significantly impacts purchasing decisions. This study contributes to understanding the commercialization of UGC and its role in shaping consumer behavior on social commerce platforms. It provides insights into how UGC marketing can be optimized to enhance trust and engagement, particularly for Chinese millennials on RED.